La traducción y lo lúdico en el cambio social: La traducción inclusiva de Morgane contra una doxa de género dominante - Monzó-Nebot, Esther; Llanos-Guerrero, Miguel (Babel, 2023)
Gender-inclusive language, both binary and non-binary, advocates for wider visibility of non-dominant genders. However, in the Spanish context, this language, especially the binary variant, has been received with much opposition led by the institution establishing linguistic norms. This paper addresses the possibility of using gender-inclusive language as a political practice in translation and explores how entertainment genres, particularly comics, and information on the social goals of heterodox linguistic practices may be conducive to relaxing the adherence to dominant doxas. By priming responses based on two gender-inclusive (one binary and one non-binary) translations of the comic Morgane by Kansara and Fert, differences between four focus groups were analyzed. Two of them received a briefing session detailing the social agenda of gender-inclusive language, and two were offered no such sessions before reading and discussing the translations. Results showed how the briefing sessions relaxed adherence to the dominant doxa even though the social purpose of gender-inclusive language was widely questioned. Further, results evinced that binary translation was more strongly opposed than the non-binary variant. It is argued that translation can be used as a tool for political and social change and become instrumental in advocating for equal opportunities for all genders.
Translation and playfulness in social change: Morgane's gender-inclusive translation against a dominant doxa
Keywords: binary gender-inclusive language; comics; doxa; focus groups; gender-inclusive translation; non-binary gender-inclusive language; Scopus; JCR